Bunyawiyah wa Rōtsiyah fī Riwayah Ahlam al-Nisāʾ al-Ḥārimī: Literal and Root Analysis in the Narrative of Ahlam al-Nisāʾ al-Ḥārimī - Qotrunnada, Junda; Ashfiya, Za’imatil (Critical Review of English-Arabic World Journal, 2024)
يحاول هذه المقالة مناقشة البنيوية للوسيان جولدمان في رواية أحلام النساء الحريم في نظرية البنيوية الوراثة، يبني جولدمان مجموعة من الفئات المترابطة، وهي الحقائق الإنسانية، والموضوعات الجماعية، والبنية، ونظرة المؤلف للعالم، والتفسير. ويستخدم الكاتب منهج البحث النوعي، وهو البحث الذي يحاول فهم المشكلة بشكل كلي من خلال الوصف.  الخطوات المستخدمة في تحليل الرواية هي: (أ)قراءة رواية أحلام النساء الحريم مرة بعد مرة. (ب)ثم فهم محتويات الرواية؛ (ج) إجراء التحليل البنيوي الوراثة رواية؛ (د) وصف نتائج التحليل. نتائج البحث في هذه المقالة هي في شكل تحليل الرواية يشير إلى الحقائق الإنسانية يعنى الحقائق الفردية والحقائق الاجتماعية ثم نظرية المؤلف للعالم في هذه الرواية.   This article attempts to discuss the structural analysis of Lucian Goldman in the novel Ahlam al-Nisāʾ al-Ḥārimī from the perspective of genetic structuralism. Goldman constructs a set of interconnected categories, namely human realities, collective themes, structure, the author’s worldview, and interpretation. The writer uses a qualitative research method, which seeks to understand the problem holistically through description. The steps used in analyzing the novel are: (a) reading the novel Ahlam al-Nisāʾ al-Ḥārimī repeatedly; (b) understanding the contents of the novel; (c) conducting a genetic structural analysis of the novel; and (d) describing the results of the analysis. The findings of this article, in the form of novel analysis, indicate the human realities—both individual and social realities—as well as the author’s worldview as reflected in the novel.